2020
DOI: 10.1016/j.polymdegradstab.2020.109305
|View full text |Cite
|
Sign up to set email alerts
|

Electronic irradiation ageing in the vicinity of glass transition temperature for PEEK space applications

Abstract: Satellites in space environment are subject to several environmental constraints. In the case of polymer materials, electronic irradiations can induce premature ageing which can lead to a shorter lifetime for the satellite. Moreover, synergistic effects between temperature and irradiation can occur and enhance this ageing. A previous study showed that PolyEtherEther-Ketone (PEEK), a newly used polymer in space industry, presents great radiation tolerance properties. Nonetheless, it was necessary to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The DMA test was performed to find the accurate T g , which was 345°C, 412°C, and close to 450°C, respectively, for samples # 4, # 5, and # 6 (Figure 12(c)). It is worth nothing that the T g has exceeded partial polyimides 9,10 and polyether ether ketone 34,35 films. These results indicated that films with ultrahigh T g had been made successfully.…”
Section: Resultsmentioning
confidence: 99%
“…The DMA test was performed to find the accurate T g , which was 345°C, 412°C, and close to 450°C, respectively, for samples # 4, # 5, and # 6 (Figure 12(c)). It is worth nothing that the T g has exceeded partial polyimides 9,10 and polyether ether ketone 34,35 films. These results indicated that films with ultrahigh T g had been made successfully.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, oxidation related peak at 1730 cm −1 enhances as a function of irradiation. On average it can be concluded that an increase in dose by two times leads to further scission and oxidation, which can be seen from the typical radiation-induced mechanical change in PEEK [ 28 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The breaking strength of PEEK reduces sharply and yield strength reduces slightly due to the 1 MeV electron irradiation with the fluences of 5 × e/ and 3 × e/ [ 27 ]. High energy electrons with the energy of 350 keV and doses of 12–34 MGy induces chemical modifications of PEEK’s macromolecules, consequently, both cross-linking, chain scission and a slight decrease of the modulus were observed by differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) [ 28 ]. However, Brillouin spectroscopy is a non-destructive, rapid and very accurate technique that allows the probing of micro or sub-nano scale perturbations in the system with the comparison of these conventional low-frequency techniques, with certain limitations regarding the measurement resolution [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Samples (PEEK films and composites) were irradiated under high vacuum by a 350 keV mono-energetic electron beam, thanks to SIRENE facility (ONERA, Toulouse, France). PEEK films were irradiated at two temperatures: room temperature and 165 °C, in continuity of our previous work, by using a heating sample-holder (its design has been already described in [18]). Composites were irradiated only at room temperature to study how the fibres influence the ageing of PEEK.…”
Section: Experimental Irradiationsmentioning
confidence: 99%
“…In previous works, we investigated the influence of electronic irradiations, carried out in spacerepresentative conditions, to the physico-chemical structure of PEEK [17,18]. We showed that electronic irradiations at room temperature induce cross-linking of the amorphous phase and amorphisation of the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%